2018
DOI: 10.5740/jaoacint.18-0121
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Determination of Aloe Polysaccharides Using Size Exclusion Chromatography Coupled with Multi-Angle Laser Light Scattering and Refractive Index Detectors

Abstract: : Size exclusion chromatography (SEC)/refractive index (RI) were used to determine molecular weight (MW) and molecular weight distributions (MWD) of polysaccharides. In aloe product research and quality control, commercially available pullulan and dextran are most commonly employed as calibration standards. Significant difference in the MW and MWD were found in literature when different methods were used. This study was to investigate the traditional methods and more recent technologies used to determine the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…MALS is used to check molar mass, polydispersity, and rms radius [ 46 ]. We found that SBP-F4 had a number-average molecular weight (Mn) of 1.986 × 10 5 g/mol, a weight average molecular weight (Mw) of 2.351 × 10 5 g/mol, and a Z-average molecular weight (Mz) of 2.867 × 10 5 g/mol.…”
Section: Resultsmentioning
confidence: 99%
“…MALS is used to check molar mass, polydispersity, and rms radius [ 46 ]. We found that SBP-F4 had a number-average molecular weight (Mn) of 1.986 × 10 5 g/mol, a weight average molecular weight (Mw) of 2.351 × 10 5 g/mol, and a Z-average molecular weight (Mz) of 2.867 × 10 5 g/mol.…”
Section: Resultsmentioning
confidence: 99%
“…The significant difference in the molecular weight and its distribution could be caused by using the PEG calibration standard. 47 Compared to the polypeptides, the The feeding composition is the stoichiometric molar ratio of Tre to the amino groups in the main chain of PEG-b-polypeptides where "Tre" refers to carboxylated trehalose. b The grafting ratio and the molecular weight M n,NMR of the synthesized glycopeptides were calculated from the 1 H NMR spectra by the integral ratio of Tre and the molecular weight of PEG-b-polypeptides.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Similarly, the molecular weights of PKDT , PKDF1T , and PKDF2T measured by GPC were 1.45 × 10 4 , 2.18 × 10 4 , and 3.10 × 10 4 with narrow distribution ( Đ ) in 2.53, 1.99, and 1.41, respectively. The significant difference in the molecular weight and its distribution could be caused by using the PEG calibration standard . Compared to the polypeptides, the higher polydispersity of glycopeptides could be found in Table and Table S1, which was presumably caused by the introduction of trehalose in GPC measurement .…”
Section: Resultsmentioning
confidence: 99%
“…Weak anion-exchangers, such as diethylaminoethyl (DEAE), tertiary amine-functionalized media [93,94] or strong anion-exchangers including quaternary (Q) amine-functionalized media [95], have been successfully utilized to purify polysaccharide sulfates. SEC is extensively employed for the measurement of total molecular masses and molecular mass distributions [96][97][98][99][100]. Moreover, this analytical technique has been effectively employed in many examples for the elucidation of fine-structures of oligosaccharides and polysaccharides [94] and to produce size classes for the determination of structure-activity relationship [101][102][103].…”
Section: Purificationmentioning
confidence: 99%
“…Weak anion-exchangers, such as diethylaminoethyl (DEAE), tertiary amine-functionalized media [93,94] or strong anion-exchangers including quaternary (Q) amine-functionalized media [95], have been successfully utilized to purify polysaccharide sulfates. SEC is extensively employed for the measurement of total molecular masses and molecular mass distributions [96][97][98][99][100].…”
Section: Purificationmentioning
confidence: 99%